Glorifying Ecocide in Cinematic Trends Versus Voicing Ecocritical Aesthetics - Shams, Ahmed Tahsin; Akter, Sanjida (SCHOLARS: Journal of Arts & Humanities, 2024)
This paper comprehensively analyzes how the environment is depicted in cinema. Portrayals contribute to normalizing such violence as a prevailing cultural trend in cinema that not only they commemorate environmental disasters as noteworthy human ‘accomplishments’ in the film but also they cultivate a concerning lack of empathy towards ecological emergencies. Spectators may perceive an ecological rape as visually captivating events, hypothetically and hegemonically. This depiction perpetuates, arguably, a distorted perspective that undermines the significance of the environmental movement. Moreover, this study reevaluates the commodification of this phenomenon, delving into how this lack of regard for the environment has evolved into a lucrative narrative device and a predetermined recipe for achieving blockbuster triumph. However, this paper concludes that alternative examples of ecocentric aesthetics are framed in a few of the 2022–2023 films where nature’s voice is not marginalized within the crowd of human voices.